(untitled) - Ariza B., F.=700 1 Hofner, M.; Barrera V., J.
(Es, En)
ilus., 13 ref.
Deteccion del virus de la estomatitis vesicular utilizando la reaccion en cadena de la polimerasa
Keywords: GANADO BOVINO; EQUIDAE; CERDO; ESTOMATITIS; VIROSIS; VIRUS DE LA ESTOMATITIS VESICULAR; PCR; DIAGNOSTICO; COLOMBIA